Finding Consensus on Integrating Neuroeducation into Trauma-Informed Counseling Practice: A Delphi Study - Jenna Epstein; Rachel McRoberts (Teaching and Supervision in Counseling, 2021)
A Delphi Study was carried out to investigate what experts considered essential components for integrating neuroeducation into trauma-informed counseling practice. After initial recruitment, a total of 14 trauma-informed counseling experts participated in a 4-round Delphi Study, in which main areas of brain education and associated educational methods were identified. Additionally, a richer description of the perceived impact of neuroeducation on clients was discussed. The results of this Delphi Study support the integration of a number of neuroeducation topics and methods into trauma-informed counseling practice and further support the need for incorporation of neuroeducation into counselor education and supervision.
Keywords: trauma-informed counseling; counselor education and supervision; neuroeducation; Delphi study; qualitative